Brussels, capital of Europe: a sustainable choice? - Philippe Van Parijs; Jonathan Van Parys (Brussels Studies, 2010)
There are many criteria which determine whether a city is a good capital. Ecological considerations lead us to place more emphasis on one criterion in particular, i.e. the more or less central location of the capital within the territory. Which European city meets this criterion best? Is the choice of Brussels as capital of the European Union likely to withstand the growing importance of this criterion and the continued enlargement towards the east? In order to answer these questions, this article defines four centres of gravity – “diplomatic”, “demographic”, “metropolitan” and “civic” – using new databases and computation techniques. Within the framework of the EU-27, Prague comes first from a “diplomatic” point of view, Frankfurt from a “demographic” point of view, Luxembourg from a “metropolitan” point of view and Brussels from a “civic” point of view. In a maximalist scenario of enlargement towards the east, this group is replaced by Vienna, Munich, Strasbourg and Brussels. The fourth criterion – which is the most favourable to Brussels – is also, on the surface, the most unstable. This article ends with a discussion of the mechanisms which are likely to ensure that Brussels will keep the “civic centrality” imparted to it historically by chance.